The Effect of Choline Chloride Supplementation on the Reproductive Performance of Simmental Bulls Fed Protected Protein in the Ration - Bambang Waluyo Hadi Eko Prasetiyono; Yon Soepri Ondho; Agung Subrata; Pramesti Kusuma Pratiwi; Mutiara Briliana Zahra; Trisna Itmamulwafa; Tertyani Kartika Pratiwi; Muslichatun Nisa; Widiyanto Widiyanto (Buletin Peternakan, 2020)
SOYXYL supplementation as a source of high-quality protected protein in rumen (Rumen Protected Protein) has proven to improve reproduction performance of bulls. The SOYXYL is an extrusion product of soybean (Glycine max) as a source of rumen protected protein. The potential of the protein supplementation is maximally expressed when it is supported by sufficient of metabolic rate. In this case the choline chloride supplementation increases the metabolic rate. The aim of the research was to analyze the effect of choline chloride supplementation on reproduction performance and hematologic status related to reproduction performance of bulls fed protected protein in the ration. The materials used were 12 bulls aged 5 years having weight of 700 ± 2.75 kg that were divided into 4 treatment groups, each of which consisted of 3 heads. The treatments applied were T0 (control): ration (grass + commercial concentrate) + protected protein supplement “SOYXYL”; T1: control + choline chloride 0.145% dry matter (DM) concentrate/head/day; T2: control + choline chloride 0.290% DM concentrate/head/day; T3: control + choline chloride 0.435% DM concentrate/head/day. Variables measured were nutrient consumption, blood lipid status, blood protein status, and reproduction performance. Data were analyzed using ANOVA in a completely randomized design and statistically processed using SAS program. The result showed that choline chloride supplementation by 0.435% from DM concentrate increased (p<0.05) the concentration of blood plasma protein, blood testosterone hormone, sperm concentration, and sperm motility from 6.44 g/dL, 4.66 ng/mL, 1006.74 million/mL, and 36.00%, respectively, in T0 to be 8.57 g/dL, 9.07 ng/ml, 1270.41 million/mL, and 70.00% in T3, respectively. The choline chloride supplementation up to 0.435% from DM concentrate to bulls supplemented with protected protein containing in the ration increased reproduction performance.